GHOSTS OF THE MUNICIPAL DEBTS’ PAST: IS MITCHELL RESURRECTING THE MATHABATHE SPECTRE? – NOT QUITE Perregrine Joseph Mitchell v City of Tshwane Metropolitan Municipal Authority (50816/14) [2014] ZAGPPHC 758 - Matome M Ratiba (Obiter, 2016)
The unfortunate choice of words by the judiciary in the case of City of Tshwane Metropolitan Municipality v Mathabathe ((502/12) [2013] ZASCA 60 (hereinafter “Mathabathe case”) has resulted in a barrage of incorrect interpretations being attributed to the decision. All of these have translated into massive uncertainty, coupled with boundless confusion as regards the whole issue of the collection of municipal debts by the municipality. Also, it had become clear to municipal entities that some of the erstwhile innovative ways of exploiting the legal framework created by the applicable legislation (eg, the withholding of certificates and demanding guarantees) have effectively been thwarted by the Mathabathe case. Responding thereto and moreover seizing upon the opportunity created by the now-existing uncertainty, municipalities have been quite inventive, and taken it upon themselves to embark on a myriad of newfound steps and methods which are generally grossly unfair and sometimes bordering on the illegal, in order to collect outstanding rates and taxes. To a large extent, the entities have been engaging in, and in fact, intensifying the long-standing practice of conducting large-scale impromptu electricity disconnections, coupled with the recent refusal to connect new owners of properties with historical debts.It was indeed a dispute arising out of such typical refusal to reconnect electricity by the municipality of the City of Tshwane that gave rise to the decision in the case of Perregrine Joseph Mitchell v City of Tshwane Metropolitan Municipal Authority (50816/14) [2014] ZAGPPHC 758 (hereinafter “Mitchell case”). Although, being a decision of the High Court, this latest decision cannot legally be expected to overrule the pronouncements made by the Supreme Court of Appeal in Mathabathe case. The Mitchell case is nevertheless considered important mainly due to its assisting in throwing new light on the issue of municipal liens, and consequently bringing a new dimension to the debate.The purpose of this note is therefore to conduct a close evaluation of the Mitchell case with a view to determining the extent to which the judgment in the case supplements or deviates from the one in the Mathabathe case. This will be done in three parts: in the first part a brief outline of the facts and decision of the Mitchell case will be rendered; the second part will provide an analysis of the relevant decision. Importantly, and in an attempt to answer the question in the title, the analysis will compare the two cases in so far as their pronouncements relate to the principles pertaining to the municipal lien. This part will also discuss and explore the important issues raised by the judgment in the case under discussion, and in the process detail the possible practical implications thereof. The last part will conclude the discussion.